The Political Socialisation and Changing Attitudes to the Role of Women: Analytical Study of Women's Image in the Libyan School Curriculum - العبيدي أمال سليمان (Dirasat in Economics and Business, 2005)
During the past three decades, the position of women and their role in society has been one of the dominant social issues in the revolutionary regime's ideology in Libya. The political socialisation process has played a significant role in changing Libyan's attitu des towards women. This was done through numbers of social lisation agents such as the education system, especially through the school curricula.